Reducing tillage does not affect the long-term profitability of organic or conventional field crop systems - Pearsons, Kirsten A.; Chase, Craig; Omondi, Emmanuel C.; Zinati, Gladis; Smith, Andrew; Rui, Yichao (Frontiers in Sustainable Food Systems, 2023)
Reducing tillage and supporting continuous living cover (CLC) can improve agroecosystem sustainability under both organic and conventional field crop production. What is less clear, however, is how reducing tillage affects the economic sustainability of organic field crop systems with CLC as compared to conventional field crop systems. To address this knowledge gap, we conducted a comprehensive economic analysis based on field records and crop yields from the long-term Farming Systems Trial (FST) at Rodale Institute in Kutztown, Pennsylvania. The FST (established in 1981) comprises three farming systems (conventional, low-input organic, and manure-based organic) which were split into tilled and reduced-till treatments in 2008. FST field activities, inputs, and crop yields from 2008 to 2020 were used to construct enterprise budgets to assess cumulative labor, costs, returns, and economic risk of six replicated theoretical farms. Reducing tillage on the conventional farms led to lower gross revenues (−10%), but lower annual costs (−5%) helped maintain similar net returns but increased economic risk as compared to tilled conventional farms. Reducing tillage on the low-input organic farms also led to lower gross revenues (−13%) and lower annual costs (−6%), which maintained net returns and increased risk relative to the tilled, low-input organic farms. For the more diverse manure-based organic farms that include periods of mixed perennial cover, reducing tillage had a smaller effect on overall costs (−2%) and no effect on gross revenues, net returns, or economic risk. Overall, reducing tillage did not affect the long-term profitability of any of the three FST farming systems. Regardless of tillage practices or organic price premiums, the manure-based organic system supported higher net returns than the conventional system. This finding suggests that continuous living cover and manure inputs may have a greater influence on system profitability than tillage practices.